By Dieudonne J.

Similar geometry and topology books

This is often the court cases of a world workshop on knot thought held in July 1996 at Waseda collage convention Centre. It used to be geared up by way of the overseas study Institute of Mathematical Society of Japan. The workshop used to be attended through approximately one hundred eighty mathematicians from Japan and 14 different international locations.

Extra info for Algebre lineare et geometrie elementaire

Example text

5. 1]. We leave it to the reader as an exercise. 1). Summing it up over A ∈ A for a finite partition A, obtain 0 ≤ Hρ (A) − a Hµ (A) − (1 − a) Hν (A) ≤ log 2. 6(a). 1). Remark. 16. 11. 5 Shannon-Mcmillan-Breiman theorem Let (X, F , µ) be a probability space, let T : X → X be a measure preserving endomorphism of X and let A be a countable finite entropy partition of X. 1 (maximal inequality). For each n = 1, 2, . . let fn = I(A|An1 ) and f ∗ = supn≥1 fn . Then for each λ ∈ R and each A ∈ A µ({x ∈ A : f ∗ (x) > λ}) ≤ e−λ .

MEASURE PRESERVING ENDOMORPHISMS is again in M (F ). The subspace M (F , T ) of M (F ) consisting of T -invariant measures is also convex. Recall that a point in a convex set is said to be extreme if and only if it cannot be represented as a convex combination of two distinct points with corresponding coefficient 0 < α < 1. We shall prove the following. 8. The ergodic measures in M (F , T ) are exactly the extreme points of M (F , T ). Proof. Suppose that µ, µ1 , µ2 ∈ M (F , T ), µ1 = µ2 and µ = αµ1 + (1 − α)µ2 with 0 < α < 1.

11. (a) There exists a finest measurable partition A (mod 0) into T -invariant sets (called the ergodic decomposition). Almost all of its components are ergodic. (b) h(T ) = X/A h(TA ) dµA (A). Proof. The part (a) will not be proved. 5). 58 CHAPTER 1. MEASURE PRESERVING ENDOMORPHISMS To prove the part (b) notice that for every T -invariant measurable partition A, for every finite partition ξ and almost every A ∈ A, writing ξA for the partition {s ∩ A : s ∈ ξ}, we obtain − h(TA , ξA ) = H(ξA |ξA )= A − ) dµA .